2014
DOI: 10.4103/0973-029x.141342
|View full text |Cite
|
Sign up to set email alerts
|

A study of salivary lactate dehydrogenase isoenzyme levels in patients with oral leukoplakia and squamous cell carcinoma by gel electrophoresis method

Abstract: Context:The enzyme lactate dehydrogenase (LDH), which is found in almost all the cells of body tissues, can be separated into five fractions and the isoenzyme pattern is believed to vary according to the metabolic requirement of each tissue. LDH concentration in saliva, as an expression of cellular necrosis, could be considered to be a specific indicator for oral lesions that affect the integrity of the oral mucosa.Aim:The present study was designed to evaluate salivary LDH isoenzyme pattern in oral leukoplaki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 20 publications
5
59
1
Order By: Relevance
“…When serum LHD values were compared among oral cancer and control subjects, we found the LDH values were significantly higher in oral cancer group than healthy controls (p = 0.001). Our findings were in accordance with those of Rathore et al, 9 Joshi et al, 11 Pereira et al, 6 Hariharan et al, 13 Muralidhar et al, 14 and Görögh et al 15 We also found that salivary LDH levels in oral cancer cases were significantly higher than in control group. The comparison of salivary LDH levels between oral cancer and healthy subjects was statistically significant (p < 0.001).…”
supporting
confidence: 83%
See 2 more Smart Citations
“…When serum LHD values were compared among oral cancer and control subjects, we found the LDH values were significantly higher in oral cancer group than healthy controls (p = 0.001). Our findings were in accordance with those of Rathore et al, 9 Joshi et al, 11 Pereira et al, 6 Hariharan et al, 13 Muralidhar et al, 14 and Görögh et al 15 We also found that salivary LDH levels in oral cancer cases were significantly higher than in control group. The comparison of salivary LDH levels between oral cancer and healthy subjects was statistically significant (p < 0.001).…”
supporting
confidence: 83%
“…18 In our study, there was a significant difference in the salivary and serum LDH levels between oral leukoplakia and healthy controls (p = 0.001). Our results were in accordance with the study conducted by Patel and Metgud, 4 Pereira et al, 6 Rathore et al, 9 Joshi et al, 11 Shetty et al, 16 and Achalli et al 19 In our present study, while comparing among all the study groups, we found that serum and salivary LDH levels were significantly higher in oral cancer followed by OSMF and oral leukoplakia. Intergroup comparison for mean value of salivary LDH levels was significantly higher in oral cancer group than control, oral leukoplakia, and OSMF groups (p < 0.0001).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…In a previous study, oral epithelium was demonstrated as the major source for saliva LDH. So, LDH salivary level could be used as a biomarker of periodontal disease (26).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, LDH is believed to vary according to the metabolic necessity of each tissue and alteration in LDH levels have been observed during development under changing biological conditions and in response to pathological processes. 68 Oxidative damage is an indicator of the diseases caused by disruption in tissue functions. The process of lipid peroxidation is under the control of efficient endogenous cellular defense systems that ensures optimum metabolic functions.…”
Section: Articlementioning
confidence: 99%